Prevalence of exercise-induced bronchoconstriction in younger swimmers’ asthmatics and non-asthmatics in a 200 meters front crawl swimming - Garcia Santos, André; Lima-Silva, Giovana; da Silva Batista-Oliveira, Alcione Patrícia; Rodrigues-Tosta, Amanda Karoline; Brandão Lopes-Martins, Rodrigo Álvaro; Oliveira Silva, Iransé; P Vieira, Rodolfo (Manual Therapy, Posturology & Rehabilitation Journal, 2022)
Background: Exercise-induced bronchospasm (EIB) present a very high prevalence among asthmatics and an increased prevalence in athletes, particularly swimmers. EIB prevalence is even higher in children. However, whether a swimming competition of 200 meters front crawl could lead to EIB in preadolescents and adolescent’s asthmatic and non-asthmatic is unknown. Objectives: Test whether a swimming competition of 200 meters front crawl could lead or detect EIB in preadolescents and adolescent’s asthmatic and non-asthmatic. Methods: Nineteen preadolescents and adolescents agreed to participate in the study, which occurred during the swimming championship of the state of Goiás. Lung function was evaluated by spirometry (FVC, FEV1, FEV1/FVC, FEF25-75%) using the Koko PFT spirometer, before and after the 200 meters front crawl. Results: The results demonstrated that for male and females, independent if there were asthmatics or not, did not present any signal of EIB or even any alteration in the lung function parameters, such as FVC, FEV1, FEV1/FVC, and FEF25-75%. Conclusions: The 200 meters front crawl, which is performed in around 2,3 minutes, did not result in exercise-induced bronchospasm in asthmatic and non-asthmatic preadolescents and adolescents.